Estimation of the crustal structure and the bedrock topography by the gravitational method around Syowa Station, East Antarctica - Nagao, Toshiyasu; Kaminuma, Katsutada (1984)
P(論文) Gravity survey was carried out at 303 stations in Lutzow-Holm Bay and in the Mizuho Plateau during the wintering in 1981. Using the gravity data, the crustal structure in the Lutzow-Holm Bay region and the bedrock topography in the Mizuho Plateau have been revealed in this study. The results are as follows : 1) In Lutzow-Holm Bay, the thickness of the crust increases from northwest to southeast. 2) In the Mizuho Plateau, at least two subglacial valleys exist near Mizuho Station, whose strike is estimated to be consistent with the flow direction of the ice sheet. 3) In the Yamato Mountains region, the crustal thickness is larger than that in the Lutzow-Holm Bay region by about 3.8km estimated from the result of simple Bouguer anomaly difference. And the difference of the crustal thickness between Syowa and Mizuho Stations is less than 2km. departmental bulletin paper